PREDICTING THE ACT OF ENGAGEMENT OF INFORMAL PRODUCTION UNITS DURING THE COVID-19 EPIDEMIC - ROUAINE , Zakaria; TAITAI , Zineb (Revue Internationale des Sciences de Gestion, 2023)
The new tax reforms have been an important support triggering the process of engagement of informal units with their tax administration. The latter has put in place various corrective measures to contain and mitigate the unfavorable consequences on the companies that make up the national economic fabric. In other words, the multilateral collaboration between the formal production units and the tax administration has allowed a successful economic recovery, increasing the resilience of enterprises during the coronavirus epidemic. However, the introduction of these new tax reforms, characterized by a downward trend in taxes, has triggered the willingness of production units operating in the informal sector to submit to the tax authorities, seizing the opportunity of the new tax bases to encourage everyone to pay taxes and improve the relationship between taxpayers and the administration. Nevertheless, this article will focus on the prediction of the act of engagement of informal units with the tax administration after the new tax reforms during the Covid-19 epidemic. This study will mobilize one of the extensions of generalized linear models, such as the binary logistic regression model.